Potential of Ethanol Extract of Red Curly Chili (Capsicum annuum L.) as an Antioxidant and Antidiabetic Agent in Mice - Safira Salsabila Citagami; Yuani Setiawati; Rochmah Kurnijasanti; Indri Safitri Mukono (Universitas Airlangga, 2025)
Medicinal plants containing polyphenols (flavonoid dan tannin), quercetin and capsaicin have strong antioxidant properties. These compounds can help inhibit oxidative stress that plays a role in various diseases, including diabetes mellitus. Capsicum annuum L is rich in phytochemicals and active compounds such as flavonoids (Quercetin, Luteolin, Kaempferol), tannins, saponins, terpenoids, carotenoids, and vitamin C. This study aimed to evaluate the potential of red curly chili (Capsicum annuum L.) ethanol extract as an antioxidant and antidiabetic agent in mice. The mice will be randomly divided into the following groups (6 mice per group): Diabetic control group (induced diabetes with streptozotocin, no treatment), and Capsicum annuum L group (Diabetic group treated with Capsicum annuum L ethanol extract at dose 100 mg/kg BW, 200 mg/kg BW, 400 mg/kg BW for 21 days). On the 21st day, the mice were anesthetized, and blood samples were collected via intracardiac puncture for the analysis of blood glucose and malondialdehyde (MDA) levels. Oral administration of Capsicum annuum L. At 400 mg/kg resulted in a significant reduction in blood glucose and MDA levels (p<0.05) compared to the diabetic group. The results approached those of the normal group, although the difference was not statistically significant. The study confirmed that Capsicum annuum L. extract effectively alleviates oxidative stress associated with type II diabetes in STZ-induced mice, as evidenced by its ability to lower blood glucose levels and reduce MDA levels.